Pengaruh Komunikasi Interpersonal Orang Tua Terhadap Data Prestasi Belajar Siswa Kelas VIII.6 SMP N 9 Padang - Zaki Kurnia Al’Qadri (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2021)
This study aims to determine the relationship between parental interpersonal communication on student achievement data in class VIII.6 SMPN 9 Padang. Communicating is a very important part in all aspects of human life, this can be seen from every event that is always related to communication. Communication that occurs between parents and children can be classified as interpersonal communication. Interpersonal communication is communication that occurs between people directly without intermediaries. Motivation is a driving force and a driving force in order to achieve maximum results in activities carried out by individuals. This type of research is applied research. The method used in this research is a survey method with a quantitative approach. This study uses a questionnaire as a research instrument. The instrument is a sheet of paper that contains several questions with a standard structure. The population of this study were students of class VIII.6 totaling 32 students, so the sample used in this study was 30 students. To determine the sample in this study using the Slovin formula. Based on this study, the results obtained from the influence of parental interpersonal relationships on student achievement data that there is a relationship between parents' interpersonal communication on interpersonal communication. This can be seen from the correlation of parental interpersonal communication to children's interpersonal communication of 0.223. And it can also be seen from the correlation of parental interpersonal communication to children's learning motivation of 0.230 with a significance value of 0.222.